FORMULATION OF CHLORPHENIRAMINE MALEATE TABLETS USING CO-PROCESSED EXCIPIENT AS A FILLER AND BINDER - Yandi Syukri; Romdhonah Romdhonah; Anisa Nur Fazzri; Rio Fandi Sholehuddin; Aris Perdana Kusuma (Sanata Dharma University, 2019)
Co-Processed Excipient (CPE) is technological innovation for tablet preparation through the direct compression method with a quick and straight forward manufacturing process because it improves the compressibility and flowability. This research aimed to formulate and evaluate of chlorpheniramine maleate tablets using spray dried CPE as filler and binder. The spray dried CPE containing MCC PH 101, and Kollidon K30 was made into tablets through a direct compression method. Meanwhile, Ludipress and Avicel PH 102 were used as filler-binder comparators. All the prepared tablet formulations were then evaluated for weight variation, hardness, friability, disintegration time, content uniformity of active ingredient, and dissolution test. The physical properties of tablets with CPE as a filler and binder produced an average weight of 151.65 1.53 mg, 5.92 0.38 kg of hardness, 0.06 0.051% friability, 520.00 2.00 seconds of disintegration time, and 99.24 0.15% content uniformity of active ingredient. The comparators indicated better disintegration time than CPE (p0.05), while the dissolution test showed that more than 80% (Q) of the amount of active ingredient was dissolved in 30 minutes. CPE could be successfully used to prepare tablet dosage form, and the tablets had fulfilled the standards of pharmacopoeia.